2014
DOI: 10.1002/ccd.25228
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term (8 year) outcomes and predictors of major adverse cardiac events after full metal jacket drug‐eluting stent implantation

Abstract: Objectives: We examined long-term outcomes and predictors of major adverse cardiac events after the full metal jacket (FMJ) stent implantation. Background: The FMJ procedure has been used to treat diffuse coronary artery disease (CAD), but long-term outcomes remain unknown. Methods: The study population consisted of 347 consecutive patients (352 lesions) who had been treated for de novo diffuse CAD with FMJ stents (stent length 60 mm). Results: The mean age was 61.0 6 10.1 years, and the stent length was 71.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…They reported that the risk of MACE was stent length >80 mm and left ventricular dysfunction [23], which were not risk factors for MACE in our study. Because our study only included RCA lesions, mean left ventricular ejection fraction in our study was within normal One serious concern in using DES is the ongoing hazard of ST.…”
Section: Discussionmentioning
confidence: 92%
“…They reported that the risk of MACE was stent length >80 mm and left ventricular dysfunction [23], which were not risk factors for MACE in our study. Because our study only included RCA lesions, mean left ventricular ejection fraction in our study was within normal One serious concern in using DES is the ongoing hazard of ST.…”
Section: Discussionmentioning
confidence: 92%
“…Substantial clinical evidence supports the efficacy and safety of percutaneous coronary intervention (PCI) using the current generation drug-eluting stents (DESs) for treating long diffuse coronary lesions [ 1 , 2 , 3 , 4 , 5 ]. However, the optimal PCI strategy and clinical outcomes remain uncertain for long lesions extending to the distal vessel segment with a diffuse small residual lumen, particularly those with an extremely small luminal diameter of ≤2.0 mm.…”
Section: Introductionmentioning
confidence: 99%
“…By extending the application of BVS to the concept of hybrid BVS-DES, the intention was reduction of eventual metallic stent burden in the coronary artery or sparring of long metallic stent. Long length of metallic stent is associated with higher rates of stent restenosis and thrombosis [3,4]. It would be of great disservice to the patient to be given permanent long metallic stents.…”
mentioning
confidence: 99%